The positional isomeric effect and structural difference in coordination assemblies system of CoII with 3/4-pmpt ligands. (1st December 2018) - Chen, Yun-kai; Tao, Ye; Ma, Yu-qi; Pang, Xu-hong; Bian, He-dong; Liu, Han-Fu; Huang, Fu-ping
Graphical abstract: Six Co(II) complexes which have different dimensionality and [Co n ] ( n  = 3 or 5) subunit were synthesized by positional isomeric ligands, the positional isomeric effect play vial roles in the structural diversity of these six complexes. The magnetic properties of two complexes which have [Co5 ] subunit have been studied. Abstract: Six Co(II) complexes were synthesized from CoCl2 with positional isomeric ligands: 3-(pyridine-3-yl)-5-(2-methoxyphenol-6-yl)-1H-1, 2, 4-triazole (3-H2 pmpt) and 4-(pyridine-3-yl)-5-(2-methoxyphenol-6-yl)-1H-1, 2, 4-triazole (4-H2 pmpt), namely, {[Co3 (3-pmpt)2 Cl2 (DMF)2 ]·(DMF)2 } n (1 ), {[Co3 (4-pmpt)2 Cl2 (DMF)2 ]·(DMF)} n (2 ), [Co3 (3-pmpt)2 Cl2 (DMF)2 ] n (3 ), [Co3 (4-pmpt)2 Cl2 (DMF)2 ] n (4 ), {[Co5 (3-pmpt)4 (HCO2 )2 (DMF)2 ]·(H2 O)4 } n (5 ), {[Co5 (4-pmpt)4 (HCO2 )2 (H2 O)2 ]·(H2 O)6 } n (6 ). Structural analysis reveals that pmpt isomers display different coordination modes to manage Co(II) ions to form [Co3 ] subunits in1 –4, and [Co5 ] subunits in5 –6, respectively. Which are further extended via different pyridine ring N-orientation to build the 1-D chains (for1, 5 and6 ) and 2-D layers (for2, 3 and4 ). Structural analysis indicate that 3/4-pmpt is an excellent multi-connect linker with pyridine ring at different angles, has an important effect on the structural topologies of such Co(II) complexes. Magnetic susceptibilities reveal weak ferromagnetic and antiferromagnetic exchange interactions between the adjacent metal centers in5 and6 .